Strategy of Cooperative Islamic Boarding School As Economic Empowerment Community - Adhi Iman Sulaiman; Chusmeru Chusmeru; Masrukin Masrukin (State Institute of Islamic Studies (IAIN) Salatiga, 2018)
The development of Islamic boarding school (Pesantren) that is no longer just to teach religion, but has become a social and economic institution with delivers the knowledge and skills of cooperative and entrepreneurship in Pesantrens. The study used qualitative method through Participatory Learning and Action (PLA). Research location in one of the largest Pesantren namely El Bayan 1 and 2, Cilacap, Cetral Java. The study determined the informant through purposive sampling i.e. the managers and members of cooperative Pesantren. Data were collected by interviews, focus group discussion, observation and documentation. Research data were analyzed with the SWOT analysis. The results showed the strategy cooperative Pesantrens in the economic empowerment of students is very important with the to improve and enhance institutional managed, membership, finance, partnerships and the development of agribusiness based business unit to enhance the well-being of Pesantren, student and the community